2013
DOI: 10.1111/ans.12397
|View full text |Cite
|
Sign up to set email alerts
|

Distal intestinal obstruction syndrome in cystic fibrosis: presentation, outcome and management in a tertiary hospital (2007–2012)

Abstract: In most patients with DIOS, the obstruction resolves with medical management. Early consultation with a CF service, assessment for a surgical abdomen and involvement of surgeons where appropriate is recommended. A history of previous laparotomy is a risk factor for the need for surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…The largest published case series found this to be necessary in only 12.5% of episodes 6. Eighty per cent of operations were complicated by significant adhesions and indeed the risk of requiring surgical intervention is higher in those who have previously undergone laparotomy,6 7 with one study finding an OR of 28.5 5. It has been suggested that the adhesions that form following prior laparotomy exacerbate the pathophysiology in DIOS, increasing the need for surgical intervention and hence early surgical team involvement is recommended 6.…”
Section: Discussionmentioning
confidence: 99%
“…The largest published case series found this to be necessary in only 12.5% of episodes 6. Eighty per cent of operations were complicated by significant adhesions and indeed the risk of requiring surgical intervention is higher in those who have previously undergone laparotomy,6 7 with one study finding an OR of 28.5 5. It has been suggested that the adhesions that form following prior laparotomy exacerbate the pathophysiology in DIOS, increasing the need for surgical intervention and hence early surgical team involvement is recommended 6.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, otras manifestaciones de la enfermedad no han logrado correlacionarse, indicando que hay factores por fuera del genotipo del CFTR que juegan un rol modulador en las complicaciones y curso de esta enfermedad de "un solo gen". Entre estos cuadros que no han sido correlacionados con la mutación del CFTR se incluyen los ya mencionados íleo meconial y síndrome por obstrucción intestinal distal, este último presentándose en niños un poco mayores 18,19,24,25 . Estos factores reguladores podrían ser ambientales, como por ejemplo influenciados por alimentación o estadía en uCI, o gené-ticos 18,23 ; la presencia de diferencias fenotípicas en hermanos y hermanos gemelos hace pensar, sobretodo, en leves diferencias genotípicas.…”
Section: Discussionunclassified
“…Risk and/or precipitating factors can include: A history of previous episodes of DIOS (10‐fold increase in risk) A history of meconium ileus at birth (almost 50% of cases) Alteration in pancreatic enzyme intake (up to 20% of cases) Dehydration or dietary change CF‐related diabetes. …”
Section: Risk Factorsmentioning
confidence: 99%
“…Additionally, lung transplantation, especially in patients with previous abdominal surgery, increases the risk of DIOS, with a reported prevalence of 10–20% . Less frequently, recent eating binges and new use of narcotic analgesia may contribute …”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation